2015
DOI: 10.1002/jaal.463
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid and Blended Learning

Abstract: Hybrid or blended learning is defined as a pedagogical approach that includes a combination of face‐to‐face instruction with computer‐mediated instruction. The terms blended learning, hybrid learning, and mixed‐mode learning are used interchangeably in current research; however, in the United States, hybrid learning is used most often. Although hybrid learning can be diverse in how it is implemented, educators agree that this approach has the opportunity to provide personalized instruction with some element of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 5 publications
(5 reference statements)
1
34
1
4
Order By: Relevance
“…Menurut Riva (2002) dalam O'Byrne (2015) pembelajaran secara sinkron merupakan pembelajaran dengan komunikasi real time seperti pada percakapan ataupun diskusi. [17]. Contoh langsung secara sinkron adalah face to face-learning, sedangkan tidak langsung (offline) secara sinkron contohnya adalah pembelajaran dengan webinar.…”
Section: Learningunclassified
See 1 more Smart Citation
“…Menurut Riva (2002) dalam O'Byrne (2015) pembelajaran secara sinkron merupakan pembelajaran dengan komunikasi real time seperti pada percakapan ataupun diskusi. [17]. Contoh langsung secara sinkron adalah face to face-learning, sedangkan tidak langsung (offline) secara sinkron contohnya adalah pembelajaran dengan webinar.…”
Section: Learningunclassified
“…Sementara pembelajaran secara asinkron mengacu pada pembelajaran dengan komunikasi di luar real time, sehingga biasanya menggunakan teks, video, atau obrolan audio. Teks dan alat digital yang mendorong pembelajaran asinkron meliputi video, papan buletin, bacaan, dan aktivitas menulis atau blog [17].…”
Section: Learningunclassified
“…Hybrid instruction, also known as blended learning or mixed-mode learning, is an instructional approach that combines face-to-face (F2F) classroom instruction and online learning activities [1]- [3]. In practice, such a definition has resulted in numerous debates among researchers and practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…see [2], [4] and [7]. A number of studies have reported on the benefits of hybrid instruction practices, such as their promotion of the flexibility of instruction [4], [8], their aiding of faculty members in terms of managing the classroom learning of large classes [7], [9], their promotion of students' personalised and learning independence Graham, 2006 as cited in [3], their improvement of students' attendance to the learning activities [10], their enhancement of students' learning achievements [11] and their facilitation of sustainable teaching and learning practices [3].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted on technology integration in professional development (Blocher, Armfield, Sujo-Montes, Tucker & Willis, 2011;Ertmer, Ottenbreit-Leftwich, Sadik, Sendurur, & Sendurur, 2012;Kopcha, 2012), as well as technology integration professional development for literacy instruction (Dwyer, 2016;Hutchison, 2012;O'Byrne & Pytash, 2015). Additionally, there has been work on the ways in which teachers' perceptions of technology influence technology integration in the classroom (Darling-Hammond, Wei, Andree, Richardson, & Orphanos, 2009;Hutchison & Reinking, 2011;Polly & Hannafin, 2010).…”
Section: New Literaciesmentioning
confidence: 99%